Harry Potter and the half-blood prince - Rowling, J.K. (New York : Scholastic, 2005)
Juvenile fiction.
Sequel to: Harry Potter and the Order of the Phoenix.
Keywords: England -- Juvenile fiction; Hogwarts school of witchcraft and wizardry (Imaginary place) -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction